Effect of codeine and loperamide on upper intestinal transit and absorption in normal subjects and patients with postvagotomy diarrhoea. Issue 3 (March 1988) - O'Brien, J D; Thompson, D G; McIntyre, A; Burnham, W R; Walker, E
Abstract : Patients with chronic severe diarrhoea after truncal vagotomy and pyloroplasty are often difficult to treat using conventional antidiarrhoeal drugs and remain severely disabled. We examined the effect of two drugs, codeine phosphate and loperamide, on upper intestinal transit and carbohydrate absorption, measured non-invasively by serial exhaled breath hydrogen monitoring, in patients with postvagotomy diarrhoea who had previously failed to gain relief from drug therapy. Orocaecal transit was consistently faster in these patients than a group of controls and was associated with malabsorption of glucose. Codeine phosphate 60 mg significantly delayed transit in patients and controls and was associated with a reduction in glucose malabsorption and improvement in symptoms. Loperamide also delayed transit and improved symptoms, but the doses required for this effect (12-24 mg) were higher than usually considered necessary in secretory diarrhoea. These studies indicate that rapid intestinal nutrient transit and associated malabsorption is a factor in the development of diarrhoea postvagotomy and that symptomatic relief can be achieved in most patients by more rational use of existing drugs.